SEPAKBOLA DI KETINGGIAN: LITERATURE REVIEW - Gaung Perwira Yustika (Jurnal Riset Kesehatan, 2018)
AbstractSoccer is often facing many various kind of situation and environmental factors, that can affects the performance of soccer players. This environmental factors can be influencing, one of them is altitude factor that can have impact to the physiology of soccer players mark by declining technical performance. This can be happen both competitive or non competitive match of soccer, researchs show a report reduction total distance cover by players (2.6-57%) when play at high intensity that can lead to hypoxia, a condition of lack oxygen at players’s body. When exercise at this circumstances, observation report greater pertubation of metabolism, plus reduction of running capacity.Fact show the different that activity with high speed and accelaration when play at 1600 m and 3600 above sea level report decrease (9-25%). And it also show the multiple effect beside decrease at speed, due to decline of partial oxygen, it also affect negative to metabolism system, because of reduction of adenosine triphosphate (ATP) at higher altitude and another system as well that lead to decrement in performance.In this review article explain altitude by collecting up to date paper information of altitude sport science and important data inside, it also inform us to know the impact factor that altitude provide to the players. That can change the way of the game and the match outcome.